Seasonal forage quality of rangelands across Kansas - Harmoney, Keith R.; Johnson, Sandra K.; Cochran, R.; Vanzant, E.; Wilson, Jeffrey J.; Yauk, D.; Holder, Michael S.; Allen, B.; Bell, Warren W.; Jansonius, H.; Jones, Timothy J.; Ploger, Mark D.; et al. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The K-State Research and Extension Forage Task Force surveyed Kansas rangelands during the course of seasonal changes to enable producers and managers to better estimate the feed value of their pasture forage during particular times of the year. Kansas’ two distinct rangeland vegetation types, shortgrass and tallgrass prairie, were evaluated. Forage samples were collected monthly from two rangeland sites in each of 10 Kansas counties. Tallgrass vegetation was lowest in acid detergent fiber (ADF) and greatest in crude protein (CP) from May to July, and rapidly increased in ADF and declined in CP the rest of the season. Shortgrass vegetation was also lower in ADF and greater in CP from May to July, but changed less from early summer to the winter than did tallgrass vegetation. Degradable intake protein (DIP) was greatest for tallgrass vegetation in May. Otherwise DIP was similar between tallgrass and shortgrass except in February and March when shortgrass had greater DIP. DIP was greatest in May and June for both vegetation types and gradually declined from June to December. Undegradable intake protein (UIP) values were greater for tallgrass vegetation than for shortgrass vegetation from May through July, but all other months were similar. Seasonal forage quality is different between and within rangeland vegetation types, and identification of dominant vegetation is a key determinant in choosing appropriate animal nutritional management strategies.
Keywords: Beef; Acid detergent fiber (ADF); Degradable intake protein (DIP); Forage quality; Ranglelands; Undegradable intake protein (UIP